2017
DOI: 10.1111/cup.12984
|View full text |Cite
|
Sign up to set email alerts
|

Random skin biopsy in the diagnosis of intravascular lymphoma

Abstract: RSB is a reliable method for diagnosis of IVL, especially in patients with FUO and any 1 or more of the 4 following abnormalities: (1) hematologic abnormalities; (2) high serum LDH; (3) hypoxemia; and/or, (4) unusual neurological symptoms with co-existing hematologic abnormalities and without lymphadenopathy, hepatosplenomegaly or BM abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…In agreement with previous reports [6,18,23,24], we found comparable age at diagnosis (67 years old) but slightly older than other Asians [4,11,20]. A slight male predominance which is consistent with studies from Thailand [11,20], Taiwan [4], and China [22] was observed in our study, although studies by Murase et al [24] and Rajyaguru et al [21] showed no gender preference. Fever was found in the majority of patients while neurologic abnormalities were also relatively common in this study.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous reports [6,18,23,24], we found comparable age at diagnosis (67 years old) but slightly older than other Asians [4,11,20]. A slight male predominance which is consistent with studies from Thailand [11,20], Taiwan [4], and China [22] was observed in our study, although studies by Murase et al [24] and Rajyaguru et al [21] showed no gender preference. Fever was found in the majority of patients while neurologic abnormalities were also relatively common in this study.…”
supporting
confidence: 93%
“…Regarding bone marrow study, although a recent series of IVLBCL patients diagnosed by random skin biopsy showed no BM involvement [11], we found approximately 35% with BM infiltration which is consistent with previous studies ranging from 26.7% to 100% [4,6,20,22,24,26,27]. Additionally, we found that increased sera LDH and ferritin were exceedingly common in IVLBCL patients, consistent with earlier publications reporting 75%-100% of elevated LDH [5,11,20,22,23,26] and 80-100% of elevated ferritin [4,26] in IVLBCL patients.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Since Ferreri et al () comprehensively described the clinical features of IVLBCL 15 years ago, the number of reported cases of IVLBCL has increased in both Asian (Pongpudpunth et al , ; Sitthinamsuwan et al , ) and Western (Cho et al , ) countries. However, due to the small sample size (Arai et al , ), heterogeneity of diagnostic modalities (Ha et al , ; Brunet et al , ), cross‐sectional design in the reported multi‐institutional studies (Ferreri et al , ; Murase et al , ; Shimada et al , ; Brunet et al , ) and early diagnosis by the use of RSB, we feel that the current studies reported in the literature do not depict an accurate clinical representation of IVLBCL.…”
mentioning
confidence: 99%
“… 9 Most Asian patients have no cutaneous lesions. 10 Even if no skin lesions are present, a random skin biopsy is a useful tool for the diagnosis of IVLBCL because it can detect tumor cells within intradermal and subcutaneous vessels. Herein, we present a case of IVLBCL that presented with hypoxemia without obvious lung lesions.…”
Section: Discussionmentioning
confidence: 99%